Indigenous Self-Determination and Applied Anthropology in Canada: Finding a Place to Stand - Asch, Michael (Anthropologica, 2022)
The discipline of anthropology has been undergoing a period of self-reflection and self-doubt. Current wisdom suggests that anthropologists do best when we act to provide context and space for the voices of others and eschew our own voices and agency. I agree wholeheartedly with aspects of this wisdom. We are at our worst when we impose our voices on others, such as by speaking for them or speaking about them as though they were not there. However, withdrawing agency does not resolve the matter. Our agency, our voice is present in all choices, even the choice not to assert it. In this paper, I discuss an approach to asserting our agency in a manner I believe to be just and justifiable. It is based on the view, following Buber and Levinas, that appropriate agency is fostered when we treat others in an I-Thou rather than an I-It relationship. I indicate, following from the work of Little Bear among others, that the notion of treaty as developed in one strain of Indigenous thought provides an articulation of the I-Thou relationship in the political realm. It fosters a political relationship based on what I term Self and Relational Other rather than Self and Oppositional Other. This form of framing promotes active agency on the part of all participants, including anthropologists.